The Critical Period of Corn Crops (Zea Mays L.) Due to Weed Competition on Various Soil Processing Systems - Girsang, Warlinson; Wibowo, Eko (International Journal of Scientific Research and Management (IJSRM), 2018)
The research was conducted in October 2016 - February 2017 at Huta Sait Buttu Saribu, Pematang Sidamanik sub-district of Simalungun district, altitude of place + 1100 m asl. The purpose of this research is to understand the critical period of corn crops (Zea mays L.) due to weed competition in various soil systems. The research implementation methodology used a split plot design (SPD) with randomized block experimental design. The treatment consists of two factors, namely the land treatment system (T) as the main plot and the weed investment period (W) as the subplot. The soil processing system consists of 3 types, i.e. without soil treatment (T0), minimum tillage (T1), and intensive tillage (T2). While the investment period of weeds is designed in 10 treatments, namely W1 = free weed for 0-15 DAP, W2 = free weed for 0-30 DAP, W3 = free weed 0-45 DAP, W4 = free weed 0-60 DAP, W5 = free weed until harvest, W6 = weeds from planting to harvest, W7 = weeds for 0-60 DAP, W8 = weeds for 0-45 DAP, W9 = weeds for 0-30 DAP, and W10 = weeds for 0-15 DAP. Each treatment was repeated 3 times. To determine the effect of the two treatments, observation towards the dominance of weeds (summed dominance ratio), the period of silk delay (day), height of plant (cm), root dry weight (g), leaf area (cm2), and dry seed production per plot (kg) is done. From the result of research data analysis, noted that soil processing system is influencing the root dry weight, plant height, total leaf area and seed production per plot, but the period of silk delay is not influenced by difference of soil processing system. The difference in weed investment time affects the period of silk delay, plant height, root dry weight, leaf area and seed weight per plot. The interaction of both treatments affects plant height, root dry weight, leaf area, and seed weight per plot. But period of silk delay is not influenced by the interaction of the two treatments. From the research results, concluded that the critical period of corn crop growth due to weed competition occurs when in the period of 0-60 DAP weeds are allowed to compete with corn crops